Job crafting towards strengths and job crafting towards interests in overqualified employees: Different outcomes and boundary effects - Zhang, Fangfang; Wang, Bin; Qian, J.; Parker, Sharon (2021)
In response to the call to investigate the positive side of overqualification, we drew on the job crafting perspective to theorize that overqualified employees can proactively regulate the discrepancies between their actual and ideal jobs via two different job crafting strategies: job crafting towards strengths (JC-strengths) and job crafting towards interests (JC-interests). We expected distinct positive outcomes for JC-strengths and JC-interests. Specifically, JC-strengths benefits both overqualified employees and the organization, whereas JC-interests only benefits the individual employees. We further proposed that the relationship between perceived overqualification and JC-strengths will be stronger when employees' organizational identification is higher, whereas the relationship between perceived overqualification and JC-interests will be stronger when their identification with the organization is lower. As expected, with the use of two-wave and dual-source data from 653 employees, we found that perceived overqualification was positively related to both JC-strengths and JC-interests; JC-strengths was positively related to both vitality and supervisor-rated task performance, whereas JC-interests was only positively related to vitality. We also found that the relationship between perceived overqualification and JC-strengths was moderated by organizational identification as hypothesized.